IMPROVING STUDENTS’ SPEAKING SKILL THROUGH PRESENTATION, PRACTICE AND PRODUCTION METHOD TO THE ELEVENTH GRADE STUDENTS OF SMA SWASTA KATOLIK BUDI MURNI 2 MEDAN - Gulo, Fanta Elpin; Sari, Anna Stasya Prima; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2020)
This research was conducted in order to improve students’ speaking skill through Presentation, Practice and Production method to the eleventh grade students of SMA Swasta Katolik Budi Murni 2 Medan. In conducting this research, the writer used Classroom Action Research (CAR). This research showed that teaching speaking skill through Presentation, Practice and Production method to the eleventh grade students of SMA Swasta Katolik Budi Murni 2 Medan could improve their speaking skill. The result of the test showed that the students’ mean score in pre-test is 58.37 with 5.71% of the students got score ≥75, in formative test the mean score is 67.45 with 32.28% of the students got score ≥75, and in post-test the mean score is 77.31 with 65.71% of the students got score ≥75. The writer concluded that Presentation, Practice and Production method could improve the speaking skill of the eleventh grade students of SMA Swasta Katolik Budi Murni 2 Medan. On the other hand, the students’ responses towards the method of the teaching sound good because above 80% of the students are interested, motivated and understand the lesson with the Presentation, Practice and Production method.